Optical detection and evaluation of partial discharge on glass insulator - Algeelani, N. A. (2013)
In this paper, assessment based on surface discharge detection and analysis on polluted glass insulators are investigated. The sparks generated due to surface discharge could produce many types of signals. In this study, the optical fibre method is used for the detection of partial discharge signals that happened due to surface discharges. Experiments on both types of clean and polluted glass insulators were used by applying the surface tracking and erosion test procedure according to IEC 60587. Considering the surface discharges a laboratory experiment was performed in which three levels of high voltages (5kV, 10kV and 15kV) were applied. In these tests fibers optic cable as a sensor along with digital processing techniques for signal processing was implemented. Then wavelet analysis was used for signal processing to recover the surface discharge signal by a fibre optic sensor. The results show that the actual signals of surface discharge are associated with the contamination levels of insulators. These results confirm that by using the fibre optic sensor technique the detection of surface discharge on the high voltage glass insulator is possible.